Gamma Knife Neurosurgery - Ganz, Jeremy (Springer Vienna : Imprint: Springer, 2011)
Today, over 500,000 patients have been treated world wide in 250 Gamma Knife Centres in 37 countries each one treating between 150 and 700 patients a year. The current book serves as a textbook, training manual and reference book for those involved in Gamma Knife practice covering the theoretical background, the practical aspects of treatment, the social side of the method and necessary information not only for users but for those who refer to the Gamma Knife. It also covers some aspects of the hospital and social administration required for optimal use of the technology, also looking at the effect of the internet on specialist medical practice.It also presents the completely new Gamma Knife (Perfexion), a new technology which extends the range of the Gamma Knife and will be the treatment standard for the future.